Do Cash Holdings and Growth Opportunities Drive Firm Investment Decisions? - Athifa, Ofigya Alethea; Lubis, Arief Wibisono (Syntax Corporation, 2026)
During 2017–2022, Indonesia suffered a liquidity crunch and financial constraints. The liquidity crunch encountered by organizations hindered their ability to pursue growth and expansion opportunities due to constrained cash flow, elevated debt levels, and the threat of bankruptcy. This study intends to examine the relationship between cash holdings and growth opportunities on investment decisions of non-financial companies in Indonesia, encompassing the periods preceding and during the COVID-19 pandemic.The Generalized Least Squares method was employed as an estimation model on panel data from 280 firms listed on the Indonesia Stock Exchange for the period 2017–2022. The results indicate that cash holdings have a negative effect on firm investment decisions. Growth opportunities exhibit a negative but insignificant effect. These findings imply that organizations tend to adopt a conservative approach when dealing with uncertain business conditions. Organizations prioritize financial flexibility by enhancing liquidity and decreasing current investments to capitalize on future profitable prospects.